Electrical and Interfacial Properties of p-Si/P3HT Organic-on-Inorganic Junction Barrier - Yakuphanoğlu, Fahrettin; Shah, M.; Farooq, W. Aslam (Polish Acad Sciences Inst Physics, 2011)
The electrical characterization of the Al/p-Si/P3HT/Ag organic-on-inorganic diode was done by current voltage, capacitance voltage and conductance voltage methods. The values of ideality factor and barrier height of the diode were determined from the current voltage characteristics and found as 2.32 and 0.77 eV, respectively. These values were also determined from Cheung's functions and Norde's method due to the non-ideal behavior of the diode. The electronic parameters obtained from the various methods indicate a good consistency with each other. The density of interface states for Al/p-Si/P3HT/Ag organic-on-inorganic diode was found to be 7.64 x 10(10) cm(-2) eV(-1). The obtained electrical parameters of the Al/p-Si/P3HT/Ag organic-on-inorganic diode are higher than that of the conventional Ag/p-Si Schottky diodes. This indicates that the electrical properties of the silicon Schottky diodes can be controlled using organic interfacial layer.
Keywords: Schottky Diode; Current-Voltage; I-V; Polymer; Parameters; Conductance; Extraction; Silicon